Safety assessment of azelaic acid and its derivatives entrapped in nanovesicles - A. Panyosak (2018)
The aim of this study was to determine the safety of azelaic acid (AA) and its derivatives in nanovesicles for pharmaceutical and cosmetic uses. The hydrophilic property of AA was modified by complexing AA with hydroxypropyl-cyclodextrin (AACD). The lipophilic property of AA was improved to diethyl azelate (DA) by esterification with Fischer reaction. AA, AACD and DA were entrapped in liposomes and niosomes with the compositions of L-±-dipalmitoyl phosphatidylcholine/cholesterol = 7:3 and Tween 61/cholesterol = 1:1, respectively, by chloroform film method with sonication. The size of the vesicles ranged from 50 to 200 nm, indicating nanosize characteristics. The cytotoxicity of AA, AACD and DA entrapped nanovesicular formulations on mouse epidermal cell lines (JB6, normal cell lines) by the sulforhodamine B assay was modest when compared with cisplatin. Blank liposomes and niosomes gave no growth inhibitory effect. The irritation of AA, AACD and DA entrapped and not entrapped in nanovesicles on rabbit skin was examined according to the Environmental Protection Agency health effect test guidelines. The results showed no signs of erythema or edema within 72 h. AA and its derivatives were safe for topical use when entrapped in nanovesicles because of no toxicity to normal cell lines and no allergy on rabbit skin.